An Awareness on Green Waste Management in Malaysia: A Web System - Ganasan, Jayasankari (IRC, 2019)
This report presents an idea of developing a web system on Green Waste Management in Malaysia, with the objective to create awareness on the importance of waste management to the society. This idea was chosen due to some critical situation today where drastic population growth of the country has led to an increase in generation of solid waste daily. Thus, “Green for Ipoh” an organisation which was started with the interest of a small group of people to do art creation especially in recycle art. In relation with that, a web system is built to help people find ways to reduce the waste produced daily. Through an interactive web page that could provide useful information on proper waste management will assist the organisation in meeting their goal. To address this issues, my research paper focus on creating with a web system which highly encourage people to dispose the waste accordingly, especially not to throw trashes to the bins instead, provide an idea of restructuring the items for future use. The main issue that society has to understand is that, it is basically a set of principles focused on waste prevention that encourage the redesign of resources life cycles so that all products are reused. The ultimate target is, no trashes are to be sent to landfills, incinerators or oceans. Since the usual way of delivering message has not reached high number of people, thus with an interactive web system where people are highly encouraged and attracted to the messages in the form of illustrations. This will create awareness on Green education for the community and in hope that our future leaders will have a better vision towards the preservation of Mother Nature. Looking at the current environmental issues, it has driven to choose this topic to produce a greener environment through a no waste practice by Green for Ipoh. At the end of project development, hoping that society especially younger generations today are more aware on waste management and know the significance of proper waste disposal in their daily routine.